Konsep Doa Yesus Menurut Kallistos Ware: Sebuah Doa Yang Mencapai Kesempurnaan - Chrisnatalia Hia; Syutriska Kardia Gulo (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
Prayer is an important aspect of human life, especially Christians. However, sometimes people pray when they are in trouble and suffering from what they are experiencing and then they need God in their lives. For this reason, the aim of the research is to explain the true power of the Jesus puja prayer and why this prayer has become an important part of Christian life based on the book written by Kallistos Ware from Diokleia. The method used by the author in this research is a literature study with a descriptive qualitative approach where the book